Cardiopulmonary resuscitation: Knowledge and personal experience among dentists in Udaipur, India - Karanprakash Singh; Nagesh Bhat; Nagrajappa Ramesh; Archana Sharda; Kailash Asawa; Anil Agrawal; Harshvardhan Chaudhary (Elsevier, 2011)
Background/purpose: The present study was undertaken to assess the knowledge and personal experience with cardiopulmonary resuscitation (CPR) among dentists in Udaipur, India. Material and methods: In a cross-sectional study, 241 dentists (113 males and 128 females) consisting 190 faculty dental practitioners of two colleges along with 51 local dental practitioners were surveyed using a self-administered, structured questionnaire pre-tested through a pilot survey. The frequency, percentage of distribution, and mean rank were calculated. Kruskal-Wallis and Wilcoxon signed-rank nonparametric tests were used to test for significance. Results: In this study, 75.9% of dentists had received information about basic CPR but only 56.0% had the correct concept of performing it, and only 12% had received practical training in basic CPR. One in ten dentists had seen patients suffering from cardiopulmonary arrest (CPA) in their practice, but none of them mentioned any fatality because of CPA. The level of knowledge was significantly higher among faculty dental practitioners (126.61) compared with local dental practitioners (100.10). In addition, a positive linear correlation was found between educational level and knowledge level (r = 0.307, P = 0.01). Conclusions: As only a few dentists (12%) had undergone training in CPR, there is a perceived need for training among dentists in its management.